PARAMETRIC STUDY ON TRANSVERSAL SLOPE AND SHORT-TERM DEFLECTION OF PRECAST SEGMENTAL BOX GIRDER CONDITIONS BY PERFORMING STATIC LOAD TEST - Mohamed Nazri, Fadzli; Mohd Yusof, Mohd Azrulfitri (Journal of Applied Engineering Science, 2018)
Precast segmental box girders (SBGs) are a new innovative construction method that has been preferred for bridge construction in the past few decades, especially in Malaysia, given its many advantages. This study mainly aims to develop an experimental-analytical methodology that can be employed by researchers, designers, and engineers in determining the condition of precast SBG bridges by performing static load test before such bridges are opened to traffic. A short-term linear elastic analysis reasonably and realistically estimated vertical deflections, bending stresses, and bending strains that considered superimposed dead load, such as parapets. Results were compared with analytical predictions via finite element method using LUSAS software. The results obtained using the proposed methodology were compared in a parametric study, followed by a variety of transversal slopes or crossfall gradients of 0%, 2.0%, 2.5% and 3.0%. The proposed methodology can accurately predict the displacements under different load cases. Moreover, stress plays a positive role in the probability effect of vertical displacement accuracy under the short-term and long-term analyses of long-span segmental bridges.
Keywords: loads; Bridging; transverse; Segmentation; displacement; construction